Comprensión y producción oral del castellano en estudiantes de lengua Ticuna en la institución educativa secundaria N° 64479 Pastor Valencia Peña Bilingüe Intercultural, Cushillo Cocha 2022 - Guerrero Sampayo, Kely Lerida (2024)
The study conducted at the secondary educational institution N° 64479 Pastor Valencia Peña Bilingual Intercultural Cushillo Cocha in 2022 aimed to examine the relationship between Spanish oral comprehension and production skills among Ticuna-speaking students. The research employed a relational methodology with a cross-sectional, bivariate field design. With a population of 307 students and a sample of 100, observation guides were utilized through survey techniques. The results indicated that students exhibited an average level in both skills, with over 70% achieving a regular level in oral comprehension and over 50% reaching a regular level in oral production.